Strategies for writing a thesis by publication in the social sciences and humanities - Nygaard, Lynn P.; Solli, Kristin (Abingdon, Oxon ; New York, NY : Routledge, 2021)
'Responding to the growing popularity of the thesis by publication within doctoral education, this book offers practical advice and critical discussion of some of the central choices and challenges that PhD students considering dissertation options face. Drawing on current research and informed by extensive experience of working with and running workshops for PhD candidates who write article-based dissertations, this book gives readers an idea of what writing a thesis by publication entails - what its purpose is, what the various expectations might be for this emerging genre, and what the challenges might be in writing one. Particular emphasis is put on how to put the individual articles together to create a coherent thesis that clarifies the student's individual original contribution. Written primarily for students, Strategies for Writing a Thesis by Publication in the Social Sciences and Humanities covers key topics such as: how the genre has developed, with an emphasis on the role of the narrative (introductory text) that accompanies the articles; typical rhetorical challenges that writers of such dissertations face; strategies for handling the writing process; specific challenges of demonstrating doctorateness in the thesis by publication and strategies for addressing them; institutional variations that the thesis writer should seek clarification on as early as possible; structural elements of the narrative and their main functions; the range of choices that can be made throughout the doctoral journey and thesis writing. This book is a must-read for PhD candidates, supervisors new to the genre, as well as those involved in directing PhD programmes who are interested in the pedagogical implications of the move towards article-based dissertations'--
Introduction: The doctorate in pieces -- The thesis by publication as an emerging genre -- The writing process : learning to juggle and finding your voice -- Demonstrating doctorateness through the narrative -- Finding out what is expected from you : rules, conventions and guidelines -- The structural elements of the narrative -- Making your doctorate your own : developing your academic identity.
OCLC-licensed vendor bibliographic record.
Keywords: Dissertations, Academic -- Authorship; Academic writing; Scholarly publishing; Doctor of philosophy degree; Social sciences -- Research -- Methodology; Humanities -- Research -- Methodology; EDUCATION / General